Women's Socio-Economic Status in The Putting-out System of Work During the Covid-19 Pandemic - Siti Lailatus Sofiyah; Emy Susanti; Sutinah Sutinah (Journal of Urban Sociology, 2023)
AbstractThis study focuses on studying the socio-economic status of women in the putting-out system of work during the Covid-19 pandemic. This work affects women in the social status and economic conditions of the family. The women of putting-out system struggle to earn income in order to survive during the Covid-19 pandemic. This study purposes analyze the socio-economic practices carried out by women during the Covid-19 pandemic. The method used in this research is qualitative with data collection techniques through observation and in-depth interviews with informants in this study. This study produces the following prepositions: first, putting-out system work improves women's social status; second, the working of the putting-out system is an arena for fighting for family survival during the Covid-19 pandemic. The researcher concludes that the social practice of putting-out system work is interrelated with the social status of women as workers, while at the same time maintaining economic sustainability for the needs of family life during the Covid-19 pandemic. Social status as a working woman is very important to increase women's bargaining power both within the family and in the local community.Keywords: socio-economic status, women worker, putting-out system work, the Covid-19 pandemic